Microbial transformation of hederagenin by Cunninghamella echinulate, Mucor subtilissimus, and Pseudomonas oleovorans. Issue 7 (3rd July 2017) - Liu, Zhen; Lu, Yan-Hua; Feng, Xu; Zou, Ying-Xin; Diao, Zhuo; Chu, Zhi-Yong
Abstract: The pentacyclic triterpenoid hederagenin (1 ) was subjected to biotransformation by Cunninghamella echinulate CGMCC 3.2000, Mucor subtilissimus CGMCC 3.2454 and Pseudomonas oleovorans CGMCC 1.1641. Three metabolites were obtained. On the basis of nuclear magnetic resonance and high-resolution mass spectral analyses, their structures were characterized as 3β, 23-dihydroxyolean-12-en-28-oic acid 28- O -β-D-glucopyranosyl ester (2 ), 3β, 15α, 23-trihydroxyolean-12-en-28-oic acid (3 ), 1β, 3β, 23-trihydroxyolean-12-en-28-oic acid (4 ), and metabolite (3 ) was a new compound. This was the first report on the biotransformation of hederagenin.